Chitosan Superabsorbent Biopolymers in Sanitary and Hygiene Applications - Peenal Arvind Mistry; Meera Nambidas Konar; Srinivasan Latha; Utkarsh Chadha; Preetam Bhardwaj; Tolera Kuma Eticha (International Journal of Polymer Science)
The consumption of diapers and sanitary products has constantly been rising. Several problems are associated with using chemical-based sanitary products, which are difficult to degrade easily and cause nappy rash and bacterial infections in babies. Therefore, there is an increasing shift towards natural-based sanitary products because of their biodegradability, non-toxicity, and biocompatibility. Several studies are being carried out in which researchers have incorporated natural polymers, such as cellulose, starch, alginate, and xantham gum for producing superabsorbent materials. Chitosan (CS) is one such natural polymer that exhibits anti-microbial activity because of the functional groups present in its structure. Moreover, it is also easily available, biodegradable, and non-toxic. This review mainly focuses on CS’s properties and several approaches to synthesizing natural polymer-based superabsorbent products, such as sanitary pads and diapers. It also briefly discusses the diversified applications of CS as a biopolymer in the cosmetic, medical, food, and textile industries. In addition, this study implies using CS as a superabsorbent biopolymer in the manufacturing and producing sanitary products for women and children. Due to the excellent water retention capacity, swelling ability, and anti-microbial activity exhibited by CS can be considered a potential candidate for producing superabsorbent biopolymers.